Does Renewable Energy Matter for Economic Growth in Central and Eastern European Countries? Empirical Evidence From Heterogeneous Panel Cointegration Analysis - Neagu, Olimpia; Haiduc, Cristian; Anghelina, Andrei (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The aim of the paper is to provide empirical evidence in support of the relationship between renewable energy consumption and economic growth in eleven Central and Eastern European (CEE) countries over the period 1995-2015 within a multivariate panel data analysis. Based on World Bank data, the panel cointegration analysis reveals that renewable energy consumption and economic growth are positively associated in the long run in CEE countries. The heterogeneous panel causality test indicates a bi-directional causality relationship in support of the feedback hypothesis between economic growth and renewable energy consumption in Central and Eastern European countries.